2015
DOI: 10.1039/c5ra09750a
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Eu3+–beta-diketonate complex-intercalated LAPONITE® with a terpyridine-functionalized ionic liquid

Abstract: Lanthanide complex-based organic-inorganic hybrid material with intense luminescence has been obtained by modifying the Eu 3+ -beta-diketonate complex-intercalated Laponite with a terpyridine moiety-functionalized ionic liquid. Remarkable luminescence enhancement as well as improved thermal-and photo-stability were observed after modification with the functional ionic liquid. The ionic liquid is believed to coordinate to and sensitize Eu 3+ ions as well as decrease proton concentration on Laponite surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…The characteristic diffraction peaks of cellulose are at 2θ = 15.0°, 16.2 and 22.5°, which are the symbolic peaks of cellulose I. The diffraction peaks of Laponite are located at 2θ = 4.4°, 20.0° and 35.0°, reflecting the crystal planes of (001), (100) and (110) [ 38 , 39 , 40 ]. According to the 2θ of (001), the basal spacing of Laponite is calculated to be 2 nm, which is much larger than the theoretical value of 0.96 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic diffraction peaks of cellulose are at 2θ = 15.0°, 16.2 and 22.5°, which are the symbolic peaks of cellulose I. The diffraction peaks of Laponite are located at 2θ = 4.4°, 20.0° and 35.0°, reflecting the crystal planes of (001), (100) and (110) [ 38 , 39 , 40 ]. According to the 2θ of (001), the basal spacing of Laponite is calculated to be 2 nm, which is much larger than the theoretical value of 0.96 nm.…”
Section: Resultsmentioning
confidence: 99%
“…1b with a, it can be observed that the C]N stretching of the pyridine ring experiences a down-shi from 1558 cm À1 to 1538 cm À1 (Dn ¼ 20 cm À1 ) upon the introduction of Eu(TTA) 3 , indicating that at least partial Terpy moieties are coordinated with Eu(TTA) 3 molecules. 13 The luminescence data of AC-Terpy-Eu(TTA) 3 were measured and displayed in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Nowadays numerous researches are concentrated on the lanthanide(III)-b-diketonate complexes (LnDCs) since this type of complexes show high luminescence intensity, good color purity and high quantum efficiency, such as the [Eu(TTA) 3 (phen)] (TTA ¼ 2-thenoyltr-iuoroacetonate), a well-known LnDCs, which has a high quantum efficiency of 36.5%. 12,13 Unfortunately, low photo-and thermo-stability severely limit their further application. A frequently-used method for solving this problem is doping LnDCs into organic/inorganic matrices like polymers, ionic liquids (ILs), polysilsesquioxanes, zeolite L or LAPONITE®, [13][14][15][16][17][18] giving rise to hybrid materials with improved photo-and thermo-stability as well as good processibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where θ is the scattering angle, λ is the wavelength of the incoming x-ray beam and n is the order), characteristic interlayer distances, d, could be calculated from the peaks of the scattering intensity I(θ) shown in Figure 4b. In the case of neat clay powder, two broad and weak patterns were observed arising from the of small thickness of the clay platelets and their local crystallinity, [53] while pristine CMC films displayed two broad peaks in I(θ) with low intensity but different positions, which arise from its semi-crystalline morphology in its dry form. [54] For the CMC-Lap nanocomposite film, we observe enhanced peak intensities, which appear to be an overlay of scattering signals due to the pure Laponite and CMC at around 2θ = 18° and 26°, while a much sharper, intense peak appeared at 5.06°, corresponding a characteristic length scale of 1.74 nm.…”
Section: Thin Film Characterizationmentioning
confidence: 98%